Neck, Shoulder and Low Back Musculoskeletal Pain in Greek Physical Education University Students: A Series of Three Cross-Sectional Studies - A. Emmanouil Analina; N. Rousanoglou Elissavet; D. Boudolos Konstantinos (Journal of Preventive Medicine And Care, 2018)
Several studies examine the musculoskeletal pain (MSP) in university students sustaining physical load as part of their compulsory learning. However, only two somewhat outdated cross-sectional studies examine the physical education teacher (PET) students. This study aimed to explore the neck, shoulder and low back MSP prevalence in Greek PET students in a series of academic years. The Nordic Musculoskeletal Questionnaire was used to record the past 12-month neck, shoulder and, low back pain, across three academic years (n = 479). The year association to MSP prevalence was examined with the cross-tabulation analysis (using the column proportion test for the year comparison) and, the gender association to MSP prevalence with the χ2 test (SPSS 22.0, p ≤ 0.05). The year association to MSP prevalence was not significant (p > 0.05). The overall prevalence was 67.6%, with multiple pain at 25.7% and, the low back presenting the highest prevalence (40.9%). Women reported a higher prevalence of neck (36%) and low back (47%) pain (p ≤ 0.05). The majority of pain and time loss duration was 1-7 days. The low back required higher medical attention (19.0%) than the neck (9.2%) and the shoulder (12.9%). The recurrent pain was at 30%, with the previous injury/accident rate at 5.8%, 14.4% and 14.6% for the neck, shoulder and low back. Our PET students present an alarming MSP prevalence. Due to their distinct work demands as PE teachers, entering working life with the healthiest possible musculoskeletal system is of critical importance. Thus, university authorities should consider strategies for the prevention of MSP risk.
Keywords: Musculoskeletal